EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS SISWA SMK NEGERI 1 BATANG ANGKOLA - Rahmadani Nasution; Eva Yanti Siregar; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2020)
Abstract This study aims to describe the effectiveness of using problem based learning (PBL) model reviewed from students’ critical thinking ability on the topic two- variable linier equation system at the tenth grade students of SMK Negeri 1 Batang Angkola. The research was conducted by applying experimental method (one group pretest post test design) with 34 students as the sample and they were taken by using simple random sampling technique from 135 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using PBL model was 2.94 (good category) and (b) the average of students’ system of two-variable linear equation system achievement before using PBL model was 50 (fair category) and after using PBL model was 91.51 (very good category). Furthermore, based on inferential statistic by using pair sample ttest (SPSS 22) and N-Gain, the result showed significant value was less than 0.05(0.000<0.05) and g=0.83 (high category). It means, PBL model was very effective used reviewed from students’ critical thinking ability on the topic two- variable linier equation system at the tenth grade students of SMK Negeri 1 Batang Angkola. Keywords: PBL model, students’ critical thinking ability